2008
DOI: 10.1212/01.wnl.0000334275.57734.5f
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in motor subtle signs among girls and boys with ADHD

Abstract: Objective To examine differences in age-related improvement in motor speed and neurologic subtle signs (overflow and dysrhythmia) among boys and girls with and without attention-deficit hyperactivity disorder (ADHD). Method Diagnosis of ADHD was determined by structured parent interview and administration of ADHD-specific and broad behavior rating scales. Motor function was assessed using the revised Physical and Neurological Assessment of Subtle Signs. Three primary outcome variables were obtained: 1) total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
117
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 31 publications
15
117
0
Order By: Relevance
“…Within-sex comparisons revealed that boys with ADHD had more overflow and more dysrhythmia than control boys (P < 0.05), while girls with ADHD in this age range did not differ from control girls. Examination of age-related change in girls versus boys with ADHD revealed that, from age 7 to 14 years, girls with ADHD demonstrate a significant reduction in overflow; while boys manifest little agerelated change during this period, suggesting that the frontal-striatal and cerebellar brain systems implicated in overflow and dysrhythmia mature earlier in girls versus boys with ADHD [Cole et al, 2008].…”
Section: Motor Development In Children With Adhdmentioning
confidence: 98%
See 1 more Smart Citation
“…Within-sex comparisons revealed that boys with ADHD had more overflow and more dysrhythmia than control boys (P < 0.05), while girls with ADHD in this age range did not differ from control girls. Examination of age-related change in girls versus boys with ADHD revealed that, from age 7 to 14 years, girls with ADHD demonstrate a significant reduction in overflow; while boys manifest little agerelated change during this period, suggesting that the frontal-striatal and cerebellar brain systems implicated in overflow and dysrhythmia mature earlier in girls versus boys with ADHD [Cole et al, 2008].…”
Section: Motor Development In Children With Adhdmentioning
confidence: 98%
“…Cole et al [2008] examined age-related reduction in subtle signs (overflow, dysrhythmia), emphasizing gender differences in 268 children of ages 7-14 years (99 boys, 33 girls with ADHD; 85 control boys, 51 control girls). Within-sex comparisons revealed that boys with ADHD had more overflow and more dysrhythmia than control boys (P < 0.05), while girls with ADHD in this age range did not differ from control girls.…”
Section: Motor Development In Children With Adhdmentioning
confidence: 99%
“…1 These developmental skills, rated using the Physical and Neurological Examination for Subtle Signs (PANESS), 2 consistently distinguish children with ADHD from typically developing (TD) children. 3 The neurobiologic underpinnings of these motor delays as well as of the cardinal ADHD behavioral symptoms are incompletely understood. A more quantitative biologically based marker is needed as a foundation for predicting risk for poor ADHD adult outcomes 4 and for designing more rational, personalized interventions that prevent these outcomes.…”
mentioning
confidence: 99%
“…The rationales for studying this age group include well-documented, ADHDrelated delays in motor skill development, 3 but incomplete understanding of the biologic basis in the motor system as well as its relationship to cognitive and behavioral data.…”
mentioning
confidence: 99%
See 1 more Smart Citation